Corporate Governance and Operational Risk: Empirical Evidence - Nsaibi, Mariem; Abidi, Ilyes; Rajhi, Mohamed Tahar (International Journal of Economics and Financial Issues, 2020)
The aim of this paper is to study the effect of governance mechanisms on the operational risk management of banks. A total of 1176 operational loss events recorded in 14 banks during the period 2006-2013 are analyzed to study the relation between the operational loss events and seven indicators of governance: the board size, the proportion of foreign administrators, the proportion of a government representative on the board, the proportion of institutional directors, the proportion of independent directors, the rotation of the director and the internal rating of the bank. The results show that only six governance mechanisms have significant effects on operational risk management. The size of the board of directors, the presence of independent directors, the presence of institutional directors, the presence of a state representative, the presence of foreign directors on the board of directors are positively and statistically significant with the severity operational losses. The results also state that the internal rating variable is negatively and statistically significant with the severity operational losses. But, the turnover hasn’t any impact on the operational risk management. Keywords: operational risk, operational loss events, corporate governance, Basel III JEL Classifications: G28, G34, G38 DOI: https://doi.org/10.32479/ijefi.9861